2017
DOI: 10.1111/psyg.12239
|View full text |Cite
|
Sign up to set email alerts
|

Association between high cumulative dose of benzodiazepine in Chinese patients and risk of dementia: a preliminary retrospective case–control study

Abstract: High-dose benzodiazepine use may be associated with dementia in the Chinese population. Prospective studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 30 publications
3
18
0
8
Order By: Relevance
“…Cheng HT et al [17] and Lee J et al [19] reported that use of Zolpidem was associated with an increased risk of Alzheimer's disease among older people, especially a high cumulative dose, while Shih HI et al [18] found that the effect of Zolpidem on cognition in patients with AD remained uncertain. Our ndings of BZDs use were consistent with several previous studies that reported long term use of BZDs increases risk of cognitive incline [10][11][12], though there were also some studies that reported no association between BZDs use and cognitive impairment [9,[13][14][15][16]. For retrospective studies, lacking well-controlling confounders, such as education level, marriage, depression, stroke, diabetes, hypertension, coronary heart disease, physical activity, smoking, medicines affected cognition, especially insomnia, is the possible cause of these inconsistent ndings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cheng HT et al [17] and Lee J et al [19] reported that use of Zolpidem was associated with an increased risk of Alzheimer's disease among older people, especially a high cumulative dose, while Shih HI et al [18] found that the effect of Zolpidem on cognition in patients with AD remained uncertain. Our ndings of BZDs use were consistent with several previous studies that reported long term use of BZDs increases risk of cognitive incline [10][11][12], though there were also some studies that reported no association between BZDs use and cognitive impairment [9,[13][14][15][16]. For retrospective studies, lacking well-controlling confounders, such as education level, marriage, depression, stroke, diabetes, hypertension, coronary heart disease, physical activity, smoking, medicines affected cognition, especially insomnia, is the possible cause of these inconsistent ndings.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of BZDs on cognition in the elderly is highly debated. Some studies have reported that long term use increase the risk of cognitive impairment [10][11][12], others have shown the contrary results [9,[13][14][15][16]. Although the association between BZDs and cognitive decline remains uncertain, it was determined that the use of BZDs in elderly should be avoided or limited for the short term.…”
Section: Introductionmentioning
confidence: 99%
“…All other studies focused on the association between BZD and dementia risk. Eight case control studies (Billioti de Gage et al, ; Chan et al, ; Gomm et al, ; Imfeld, Bodmer, Jick, & Meier, ; Takada, Fujimoto, & Hosomi, ; Tapiainen et al, ; C.‐S. Wu, Ting, Wang, Chang, & Lin, ; C.‐S.…”
Section: Resultsmentioning
confidence: 99%
“…All other studies focused on the association between BZD and dementia risk. Eight case control studies (Billioti de Gage et al, 2014;Chan et al, 2017;Imfeld, Bodmer, Jick, & Meier, 2015;Takada, Fujimoto, & Hosomi, 2016;Tapiainen et al, 2018;C.-S. Wu, Ting, Wang, Chang, & Lin, 2011;C.-S. Wu, Wang, Chang, & Lin, 2009) and four cohort studies (Billioti de Gage et al, 2012;Gallacher et al, 2012;Gray et al, 2016;Shash et al, 2016) showed a significant association between chronic BZD use and increased risk of dementia.…”
Section: Benzodiazepinesmentioning
confidence: 99%
“…Uma associação positiva pode ser explicada pelo fato de que a exposição foi motivada pelos primeiros sintomas da doença (VERDOUX et al, 2005;COELHO et al, 2006;BILLIOTI DE GAGE et al, 2015). Um recente estudo caso-controle com 91 indivíduos caso e 182 indivíduos controles com idade igual ou superior a 75 anos, observou que indivíduos chineses podem desenvolver demência quando administram altas doses de benzodiazepínicos (CHAN et al, 2017).…”
Section: Introductionunclassified